P715 Opioid use in patients with inflammatory bowel disease. (16th January 2018) - Lin, X; Lofland, J; Zhang, L; Lee, K; Sloan, S; Chamaa, L; Marano, C; Plevy, S
Abstract: Background: Inflammatory bowel disease (IBD) mainly comprises two chronic inflammatory disorders of gastrointestinal tract: Crohn's disease (CD) and ulcerative colitis (UC). Data on pattern of opioid use in IBD patients (patients) in a real-world setting would provide information to understand disease and pain management. Objectives are to estimate rates of narcotic opioid use in IBD patients prior to and after IBD diagnosis and to explore the relationship between opioid use and healthcare resource utilisation. Methods: Retrospective analysis of Truven Commercial Claims and Encounters Database between January 1, 2006 and December 31, 2016 was conducted. Patients with 3-year continuous enrolment (1 year prior to first IBD claim = year 0, first year after first IBD claim = year 1, and second year after IBD claim= year 2) and at least two claims of CD or UC during year 1. Patients were classified into CD or UC cohort if majority of IBD claims were CD or UC, respectively. The first IBD claim was used as index date. A non-IBD cohort was matched by age, gender, index date and state. Descriptive statistics were used to summarise patient characteristics. Generalised estimating equation (GEE) and logistics regression were used to estimate rates of opioid use over time and odds ratios (OR) of having inpatient stay (IP) or emergency room visit (ER) in year 2 between year 1 opioid users and non-users, respectively. Results: CD cohort ( n = 19904) had mean age of 39 (SD 15.7) years, mean Quan-Charlson Comorbidity Index (QCI) score of 0.71 (SD 1.96), 55% were female. UC cohort ( n = 25084) had mean age of 43 (SD 13.9), mean QCI score of 0.70 (SD 2.11), 54% were female. GEE estimated %patients with opioid claim during years 0, 1, and 2 (Table 1). For CD cohort, 27.4% opioid users vs. 12.2% non-users had CD-related ER and 34.5% of opioid users vs. 16.3% of non-users had CD-related IP during year 1. For UC cohort, 15.3% opioid users vs. 6.3% non-users had UC-related ER and 25.7% opioid users vs. 11.2% non-users had UC-related IP during year 1. Adjusted for age, gender, and QCI score, the ORs (95% CI) of having IP in year 2 between year 1 opioid users and non-users are 1.9 (1.7, 2.1) for CD and 1.8 (1.6.2.0) for UC. ORs (95% CI) of having ER in year 2 between year 1 opioid users and non-users are 2.0 (1.8, 2.2) for CD and 1.7 (1.5, 1.9) for UC. Conclusions: IBD patients have higher opioid use vs. non-IBD patients. In both CD and UC cohorts, first year following IBD diagnosis appears to have higher rates of opioid use than those of the year before diagnosis and the second year after diagnosis. Opioid use may be associated with an increased risk of IP and ER visits. These data suggest there may be a need for better disease management among patients with IBD.